PENGARUH PENGGUNAAN TEKNIK THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 31 PADANG - Putri, Ranti Dwi; R., Syahrul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this study there are three. First, describe the skills of writing fable text of grade VII students of SMP Negeri 31 Padang before using Think Talk Write (TTW) technique. Second, describe the skills of writing fable text of grade VII students of SMP Negeri 31 Padang after using Think Talk Write (TTW) technique. Third, analyze the influence of Think Talk Write (TTW) technique to the writing skill of fable text of grade VII students of SMP Negeri 31 Padang.Â Kata Kunci: Pengaruh, Teknik Think Talk Write, Teks Fabel